Path analysis of jabuticaba tree fruit traits - Salla, Vanessa Padilha; Danner, Moeses Andrigo; Citadin, Idemir; Sasso, Simone Aparecida Zolet; Donazzolo, Joel; Gil, Bruna Valéria (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to identify the direct and indirect effects of jabuticaba (Plinia cauliflora) fruit traits on pulp yield and anthocyanin content in the peel. Fruit from 36 jabuticaba trees were collected at five occurrence sites in the Southwestern region of the state of Paraná, Brazil. Different path analysis strategies were used in the evaluation of the following fruit traits: weight and diameter; pulp yield; seed and peel percentages; contents of total soluble solids, titratable acidity, anthocyanin, and flavonoid; and number of seeds per fruit. Ridge path analysis strategy had better performance than the analysis with the exclusion of traits, particularly under the presence of severe multicollinearity in the data set. Pulp percentage and total soluble solid content can serve as indirect selection parameters for increasing anthocyanin content in jabuticaba peel. Peel percentage is the main trait with determinant effect on jabuticaba pulp percentage, and the indirect selection for fruit with smaller amount of peel can be effective to increase pulp yield.
Keywords: Plinia cauliflora; anthocyanin; multicollinearity; ridge path analysis; pulp yield; indirect selection